2018
DOI: 10.1074/jbc.ra117.001049
|View full text |Cite
|
Sign up to set email alerts
|

Loss-of-function PCSK9 mutants evade the unfolded protein response sensor GRP78 and fail to induce endoplasmic reticulum stress when retained

Abstract: The proprotein convertase subtilisin/kexin type-9 (PCSK9) plays a central role in cardiovascular disease (CVD) by degrading hepatic low-density lipoprotein receptor (LDLR). As such, loss-of-function (LOF) PCSK9 variants that fail to exit the endoplasmic reticulum (ER) increase hepatic LDLR levels and lower the risk of developing CVD. The retention of misfolded protein in the ER can cause ER stress and activate the unfolded protein response (UPR). In this study, we investigated whether a variety of LOF PCSK9 va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 54 publications
(85 reference statements)
0
20
0
Order By: Relevance
“…To block Smad3 expression, siGENOME SMARTpool siRNA targeted against Smad3 (UCAAGAGCCUGGUCAAGAA, GAGUUCGCCUUCAAUAUGA, GGACGCAGGUUCUC-CAAAC, GGACGAGGUCUGCGUGAAU) was purchased from Dharmacon (SO-2782081G). 100 nM of siRNA targeted against Smad3 or scrambled siRNA control was transfected using RNAiMAX (ThermoFisher Scientific) as described previously [26].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To block Smad3 expression, siGENOME SMARTpool siRNA targeted against Smad3 (UCAAGAGCCUGGUCAAGAA, GAGUUCGCCUUCAAUAUGA, GGACGCAGGUUCUC-CAAAC, GGACGAGGUCUGCGUGAAU) was purchased from Dharmacon (SO-2782081G). 100 nM of siRNA targeted against Smad3 or scrambled siRNA control was transfected using RNAiMAX (ThermoFisher Scientific) as described previously [26].…”
Section: Methodsmentioning
confidence: 99%
“…Whole cell and tissue lysates were prepared using SDS lysis buffer containing a protease inhibitor cocktail (Roche), and protein concentration was measured as described previously [26]. The samples were resolved using SDS-PAGE and subsequently transferred to nitrocellulose membranes.…”
Section: Methodsmentioning
confidence: 99%
“…3B and C). Our research group has also used the TBCD assay described in this report to demonstrate changes in cell death in HK2 cells transfected with mammalian expression plasmids [2].
Fig.
…”
Section: Methods Validationmentioning
confidence: 99%
“…It was until 2015, Poirier et al (2015) demonstrated that GRP94, an ER chaperone specifically interacts with PCSK9 and blocks its interaction with LDLR. Interestingly, it was later identified that GRP94 chaperones PCSK mutant pro-forms in ER and alleviate the potential toxic ER-stress ( Lebeau et al, 2018 ). The underlying mechanism was further delineated to GRP94 interaction with mutant PCSK9 which prevents the latter’s binding to GRP78, an ER luminal chaperone that signals proteotoxic stress in ER to major ER stress sensors ( Lebeau et al, 2018 ).…”
Section: Deregulation Of Er Homeostasis and Activation Of Upr By Ldlrmentioning
confidence: 99%
“…Interestingly, it was later identified that GRP94 chaperones PCSK mutant pro-forms in ER and alleviate the potential toxic ER-stress ( Lebeau et al, 2018 ). The underlying mechanism was further delineated to GRP94 interaction with mutant PCSK9 which prevents the latter’s binding to GRP78, an ER luminal chaperone that signals proteotoxic stress in ER to major ER stress sensors ( Lebeau et al, 2018 ). In a way, contradicting to the blocker role of GRP94 in PCSK9-LDLR interactions, PCSK9 is also reported to act as a chaperone for LDLR.…”
Section: Deregulation Of Er Homeostasis and Activation Of Upr By Ldlrmentioning
confidence: 99%